Marketing de experiência no São Paulo Fahion Week: estratégias que conectam marcas e consumidores - Paiva, Juliana Valle Viana Marques (2025)
This dissertation investigates the impacts of experiential marketing strategies implemented by brands during São Paulo Fashion Week (SPFW), with a specific focus on activations promoted at the booths of participating companies during the 2024 edition, held from October 14 to 21. The central research question is: what are the impacts of the experiential marketing actions proposed by brands that set up booths at the event? To address this, two hypotheses were proposed: (a) immersive and sensory experiences positively influence participants’ perceived value and purchase intent; and (b) brands offering meaningful and personalized interactions are more likely to be remembered by attendees after the event compared to those that do not invest in such activations. This is an exploratory, qualitative study that employed direct observation across all days of the N58 edition of SPFW, along with the application of structured questionnaires to event attendees. The use of questionnaires was chosen due to the fast-paced nature of the event, where participants' time is limited. According to Gil (1999), this method is particularly effective in contexts that require quick and standardized data collection, such as large-scale events. The theoretical foundation draws on authors such as Kotler et al. (2024), Schmitt (1999), Carù and Cova (2007), and Pine II and Gilmore (1999), who explore experiential marketing, consumer behavior, the experience economy, and the sensory-emotional dimensions that connect people to brands. These concepts were cross-referenced with the data collected at SPFW 2024, revealing valuable insights into consumer perceptions of brand activations. On-site booth observations enabled the identification of creative strategies, interaction formats, and varying levels of audience engagement. The findings demonstrate that experiential marketing at SPFW played a significant role in enhancing brand image, fostering emotional connections, encouraging social media engagement, and strengthening post-event brand recall. The study further emphasizes the strategic importance of events in creating memorable brand experiences and in contributing to the symbolic value of companies within the creative economy ecosystem.